ANÁLISIS DE LA CALIDAD DEL SERVICIO QUE PRESTA LA HOSTERÍA TIERRA DORADA DEL CANTÓN YANTZAZA, PROVINCIA ZAMORA CHINCHIPE - Tene Pauta, Verónica Liliana (2020)
Over time it has been evidenced that the hotel industry has been immersed in a constant change and evolution. For hotel companies, it is very important to deliver a quality service to satisfy the customer, since they are in a competitive environment. The hotel company quality service must be optimal to engage greater customer receptivity, because this industry is constantly growing. In the city of Yantzaza you can witness the growing tourist activity; however, currently the hotel area does not have studies regarding the quality of service, due to the lack of interest of the owners, lack of control of regulatory entities, also because of the low level of importance to the issue of quality in the provision of services field. Due to this reality, it was decided to carry out the present research work, entitled: “Analysis of the quality service provided by the Hostería Tierra Dorada of the canton Yantzaza, province Zamora Chinchipe”, with the purpose of analyzing the quality of the service provided by the inn. In order to carry it out, it was necessary to set up some objectives that allow the develop of the research in the best possible way. As the main objective of the research it was considered: “To analyze the quality of the service provided by the Hostería Tierra Dorada of the Canton Yantzaza, province Zamora Chinchipe”, in addition, for the development of the aforementioned objective, three specific objectives were established allowing the investigation to be fulfilled. The first specific objective consists in: “Carrying out the diagnosis of the quality service of the Hostería Tierra Dorada of the canton Yantzaza, province Zamora Chinchipe”, an analysis of the environment of the inn was carried out with the purpose of knowing the current situation of it, applying a diagnostic matrix and in turn an interview aimed at the company staff. The second specific objective is to: “Evaluate the quality of the customer service offered by the Hostería Tierra Dorada of the canton Yantzaza, province Zamora Chinchipe”, a questionnaire based on the SERVQUAL Model was applied, thus allowing to obtain external data from the inn, in order to evaluate the quality of the service provided to customers. The third specific objective consists in: “Proposing strategies for the improvement of the quality service of the Hostería Tierra Dorada of the canton Yantzaza, province Zamora Chinchipe”, for the fulfillment of this objective, some proposals were made to define the strategic points that will allow the improvement of the quality service provided by the inn. Furthermore, for the develop pment of the methodology, the analytical method was considered, in order to analyze the result of the diagnostic matrix, the interviews and surveys applied to the staff and clients of the hostel respectively. Likewise, the synthetic method was applied to reconstruct the information collected. And the inductive and deductive approach were also used, which allowed establishing the information obtained through books, theses, among others to determine the strategies, conclusions and recommendations. A diagnostic matrix was developed and a direct observation was applied, these techniques allowed obtaining information on the current situation of the inn; moreover, the descriptive method was used, in order to describe the information obtained during the investigation. On the other hand, a survey was applied to the clients of the inn, which was based on 5 the SERVQUAL model questionnaire, considering as a sample 100 surveys to be applied, in the same way the quantitative and qualitative approaches were used, which allowed describing the results obtained from surveys numerically through tables and graphs. The SWOT Matrix (Strengths, Opportunities, Weaknesses and Threats) was prepared, which allowed establishing both internal and external factors of the inn, after this the Matrix of Strategies (SWOT - Crusade) was developed, through which strategies were established to Service improvement. Likewise, the participatory method was useful to inform the owners of the inn the results obtained in the investigation. Finally, a Strategic Objectives Format was established to develop the proposals for the improvement of the quality service provided by the inn, it was indispensable the use of human, material and technological resources. In the first specific objective, from the results obtained, it can be evidenced that the hotel meets the majority of the Regulatory Entities requirements, but nevertheless it still has a deficiency in some of the requirements for the correct operation of the hotel company. In the second specific objective it can be determined that customers are not fully satisfied with the services received. Finally, regarding the third specific objective, the proposal of the strategic objectives for a better quality of service was developed. It is concluded that the inn meets 81.82% of the requirements demanded by regulatory entities, so there is some deficiency in compliance with requirements of entities such as the National Secretariat for Risk Management, CONADIS, Ministry of Environment, Ministry of Labor and MINTUR. Likewise, it is determined that 45.91% of the clients are satisfied with the services received, as well as it is concluded that, regarding the failures found in the investigation, strategies were established focused on improving the quality of the service offered by the inn. Finally, it is recommended that the owners of the inn fully comply with the requirements required by the different regulatory entities. It is also recommended to be interested in measuring the level of customer satisfaction in relation to the services received, because, when finding flaws in the company, these weaknesses cannot be underestimated because they are determinants for the dissatisfaction and loss of customers. In the same way it is recommended to make the proposals developed for a better quality of the hostel service, because the clients are the fundamental basis for its growth, thus allowing greater demand, greater business profitability and thus also contribute to the sustainable tourism development of the canton and province; likewise benefit the local quality of life.